The Analysis of Figurative Language Found in the Prestige Movie - Al-Faruq, Jasir; Putra, Octa Pratama (Journal of linguistics, culture and communication, 2024)
This research is to analyze the figurative language found in the The Prestige movie. In the movie, the use of language is essential as the tool to communicate with each other. About language, figurative language is one kind of language variety. Figurative language dramatically improves the way humans communicate meaning. The analysis and discovery of the figurative language utilized in the film The Prestige was the primary goal of this study. The purpose of this study is to identify the kinds of figurative language that are used in this film. It also seeks to identify the most often-used metaphorical language in this film. This study's author employs a qualitative methodology, which falls under the library research category. The dialogue from the film The Prestige serves as the research's data source. As a result, seven categories of figurative language were identified by the study's findings. Seven kinds of figurative language are found in the total of selected either monologue or dialogue that contains a figurative language. The figurative language found are: personification (6 data), hyperbole (9 data), metaphor (5 data), simile (2 data), and paradox (1 data). Based on the data gathered and examined, hyperbole appeared in nine data points. The hyperbole of figurative language used is the most common form in this movie.